Business model analysis of the carbon dioxide removal sector: Case study of three companies in Iceland - Guðlaug Geirsdóttir 1965- (2024)
Studies regarding sustainability in business models of carbon dioxide removal companies are limited. Consequently, thus a relevant knowledge gap exists. To examine this gap, an exploratory case study was conducted with the aim of understanding how sustainable and innovative business models are for such companies and exploring the ties between sustainable innovation in business models and strategies. The study is based on qualitative research, both available secondary data and interviews with individuals who work closely with companies in the industry. This study provides valuable information about the activities of such companies, as it offers an overview of the sector's operation. The sustainability of Icelandic carbon dioxide removal companies was analysed with reference to a sustainable business model canvas. The study concludes that the companies studied consider sustainability-related factors by utilising their resources, capabilities, innovation, and effectiveness to maximise their impact and support growth that is based on sustainable customer value. A major driver for companies to engage in sustainable innovation is a European Union certification as the certification is crucial for companies to receive grants from the EU Horizon Europe program. Companies are primarily driven by factors that add value for themselves and their customers, while any value for other stakeholders is considered secondary. Due to increased market demand, they are motivated to lead the way and drive changes towards a more sustainable and innovative future for both customers and partners. There is, however, limited data on how companies strategies impact the business models and actions. However, there are some similarities between the strategies, activities, and business models of the analysed companies. The practical and theoretical contribution of this study is to present two new useful models or further studies, one for analysing drivers for sustainable innovation and another for analysing how companies' strategies affect ...